ANIFROLUMAB IN THE TREATMENT OF SYSTEMIC LUPUS ERYTHEMATOSUS - A LITERATURE REVIEW - Dawid Nowicki,; Paulina Małyszczak,; Małgorzata Muszyńska,; Julia Surowaniec,; Katarzyna Karaś,; Sylwia Mroszczyk, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and objective: Systemic lupus erythematosus (SLE) is a chronic, autoimmune disease characterised by a diverse clinical course and multifactorial aetiology. Improvement in treatment has been significant in recent years. Current treatment is primarily based on glucocorticosteroids and immunosuppressive drugs that cause numerous side effects and have limited efficacy in a significant number of patients. Anifrolumab therapy is a new treatment option in SLE. The aim of this review is to describe its characteristics, mechanisms of action, and therapeutic effects.Review methods: A literature review was conducted using scientific publications, focusing primarily on those published between 2017 and 2025. The PubMed and Google Scholar databases were used for the search. Publications in English and Polish that met thematic and substantive criteria were analyzed. Ultimately, 32 publications were included in the reviewBrief description of the state of knowledge: Anifrolumab is a modern monoclonal antibody that blocks the type I interferon pathway, one of the key mechanisms in the pathogenesis of SLE. A significant reduction in disease activity, improvement in joint and skin symptoms, and a reduction in glucocorticosteroid use can be achieved.Summary: Anifrolumab represents a novel approach in the treatment used in moderate to severe forms of SLE. This drug improves skin and joint symptoms, reduces disease activity, and reduces used doses of corticosteroids. It is well-tolerated and has a rapid therapeutic effect. It improves patients' quality of life. However, its safety in use in children, pregnant and breastfeeding women is unknown.